Japanese family-style recipes - Urakami, Hiroko (Kodansha International, 1992)
This beautifully illustrated collection of fifty-three recipes represents the best of Japanese home cooking, ranging from soups and main dishes to snacks and desserts. You'll find mouth-watering Chicken-and-Egg Donburi, delicious Yellowtail Teriyaki, and simple yet satisfying Salmon Tea Rice. Dishes Westerners have come to love include that simmering cauldron of beef, tofu, and vegetables known as sukiyaki; grilled chicken kebabs (yakitori); and crispy vegetable tempura.